The decline (and revival?) of black farmers and rural landowners : a review of the research literature - Gilbert, Jess Carr; Sharp, Gwen; Felin, M. Sindy (Land Tenure Center, University of Wisconsin-Madison, 2001)
African-Americans as a group went from owning almost no land in the United States after the Civil War to peaking at 15 million acres by 1920. In that year, 14% of all US farmers were black. Of these 926,000 black farmers, all but 10,000 were in the South. By 1997, fewer than 20,000, or 1% of all farmers, were black, and they owned only about two million acres. The loss of landownership and farming operations has contributed to the poverty of many rural communities in the South. This paper consists of a review of 74 journal articles, reports, chapters, and books on African-Americans and farming, comprising most of the scholarly literature on the issue published since 1971. One of the commonalities in the literature is the sense of hopelessness in stemming the tide of black land loss. On the other hand, another commonality is the view that the black farmer and rural landowner must be sustained, even brought back. Among the studies are those claiming that landowners make up the backbone of civic and political life in rural black communities. Other advantages of landownership include increased personal pride, higher educational achievement of children, and an overall better sense of wellbeing. Most of the works offer similar perspectives of the decline of blacks in farming, and suggested solutions also are often repeated in these works. But there are differences in the works, and together they cover a wide range of issues that differentiate black farmers by sub-region, state, farm size, tenure, crops raised, and social and economic situation.
iii, 22 p.
Keywords: African American farmers Government policy United States Bibliography; African American landowners Bibliography; Farm ownership United States Bibliography; Agrarian structure United States Bibliography